2020
DOI: 10.1063/5.0009596
|View full text |Cite
|
Sign up to set email alerts
|

Mg diffusion and activation along threading dislocations in GaN

Abstract: The precise control of p-GaN is a crucial issue for developing GaN-based power devices. Mg as an acceptor is commonly used in p-type doping; however, the Mg diffusion through threading dislocations (TDs) has not been well addressed. To clarify the Mg diffusion and activation along TDs, we have performed a systematic characterization of a Mg-implanted homoepitaxial GaN layer grown on a freestanding substrate. Active-Mg related donor-acceptor pair (DAP) emission from certain TDs is identified by cathodoluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…Recently it was reported that Mg diffuses into the n-type GaN through the dislocations [57]. Because of diffusion of the Mg along the dislocations, the Mg doping level can be reduced to 10 16 cm −3 [58]. Moreover, for this doping level of 10 16 cm −3 , Mg dopants have an activation energy of about 0.25 eV [59], close to the one extracted from T 1 peak.…”
Section: Discussion On Defect Statessupporting
confidence: 60%
“…Recently it was reported that Mg diffuses into the n-type GaN through the dislocations [57]. Because of diffusion of the Mg along the dislocations, the Mg doping level can be reduced to 10 16 cm −3 [58]. Moreover, for this doping level of 10 16 cm −3 , Mg dopants have an activation energy of about 0.25 eV [59], close to the one extracted from T 1 peak.…”
Section: Discussion On Defect Statessupporting
confidence: 60%
“…Then, the same slope of about 0.0017 for Samples A and B″ demonstrates that the Fe diffusion flux is not relevant to the Fe doping concentration, 3D growth mode, and the edge-type TD densities. It is interesting to note that Mg diffusion along the edge- and mixed-type TDs was evidenced [ 37 ]. However, our current study reveals that the edge-type TDs densities are not the key factor on Fe diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…For the CL measurements, cross-sectional specimens were prepared by a novel angle cutting method, the details of which are described elsewhere. 19,34 The CL measurements were conducted using a HORIBA MP32 CL system attached to a Hitachi SU6600 field emission scanning electron microscope (FESEM) at an incident energy of 3 kV and a specimen temperature of 78 K.…”
Section: Methodsmentioning
confidence: 99%